Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Keywords: GILL, Stephen; political science / globalization; political science / reference